Adverse Reactions to Antituberculosis Drugs in Iranian Tuberculosis Patients. (24th November 2014) - Farazi, Aliasghar; Sofian, Masoomeh; Jabbariasl, Mansoureh; Keshavarz, Sara
Abstract : Background . Antituberculosis multidrug regimens have been associated with increased incidence of adverse drug reactions (ADRs). This study aimed to determine the incidence and associated factors of ADRs due to antituberculosis therapy. Methods . This is a retrospective cross-sectional study on tuberculosis patients who were treated in tuberculosis clinics in Markazi province in Iran. The information contained in the medical files was extracted and entered into the questionnaire. Data was descriptively analyzed by using statistical package for social sciences (SPSS 18). Results . A total of 940 TB patients of 1240 patients' medical records available in 10 medical offices were included in this study. Of the 563 ADRs found in this study, 82.4% were considered minor reactions and 17.6% were major reactions. No death from antituberculosis ADR was observed. We found that the risk of major ADRs was higher in females (P   value = 0.0241 ), age >50 y (P   value = 0.0223 ), coinfection with HIV (P   value = 0.0323 ), smoking (P   value = 0.002 ), retreatment TB (P   value = 0.0203 ), and comorbidities (P   value = 0.0005 ). Conclusions . This study showed that severe side effects of anti-TB drugs are common in patients who have risk factors of ADRs and they should be followed up by close monitoring.